Challenges of maternity continuum of care within the primary health care in northwest Ethiopia: interpretive description using a socio-ecological model - Mihret, Muhabaw Shumye; Alemu, Kassahun; Beshah, Debrework Tesgera; Gezie, Lemma Derseh; Erlandsson, Kerstin; Lindgren, Helena (Frontiers in Public Health, 2024)
BackgroundThe maternity continuum of care plays a vital role in improving maternal and neonatal outcomes. However, its uptake remains low in Ethiopia, highlighting the need to identify challenges within the primary health care system to inform practice. Hence, this study aimed to explore the challenges of the maternity continuum of care within the primary health care system in northwest Ethiopia.MethodsAn interpretive description approach was employed from March 3, 2022, to November 27, 2022, within the primary health care system in northwest Ethiopia. Maximum variation sampling was utilized, comprising 28 in-depth interviews, three focus group discussions with 29 participants, and four key informant interviews. The reflexive thematic analysis method was applied, and the results were mapped onto the constructs of the socio-ecological model.ResultsThe analysis identified four main themes: low maternity healthcare-seeking behavior (intrapersonal level), lack of peer and family support (interpersonal level), cultural influences on maternity care and low community responsiveness (community level), and inadequate health system readiness and response (health facility/system level). Some of the sub-themes include low health literacy and self-efficacy and misconceptions regarding maternity care at the intrapersonal level; peer and family pressure against seeking maternity care, low autonomy, and intimate partner violence at the interpersonal level; cultural influences on pregnancy disclosure and postnatal care and low social accountability at the community level; and delays in accessing ambulance services, long waiting times for maternity care, shortages of essential healthcare supplies, poor coordination of care, inadequate monitoring and evaluation, disrespectful maternity care, and dissatisfaction among healthcare workers at the health facility/system level.ConclusionIntrapersonal, interpersonal, community, and health facility- and system-level challenges have influenced the maternity continuum of care within the primary health care in northwest Ethiopia. Since these challenges are interdependent, considering a holistic approach within primary health care could lead to an improved maternity continuum of care.